Genomic diversity of two lineages of exfoliative toxin A-converting phages predominating in Staphylococcus aureus strains in the Czech Republic - Holochová, Pavla; Růzicková, Vladislava; Pantůcek, Roman; Petrás, Petr; Janisch, Roman; Doskar, Jirí (Research in microbiology, 2010)
We have isolated and characterized two distinct types of exfoliative toxin A (ETA)-converting bacteriophages originating from Staphylococcus aureus strains responsible for massive outbreaks of pemphigus neonatorum in the Czech Republic. Three induced phages designated as ph iB531, phi B557 and phi B122 were found to be capable of transferring the eta gene into the prophageless non-toxigenic S. aureus strain and converting it into an ETA producer. Comparisons of the phage sequences derived from 12 selected genes and 2 genomic segments (polymorphic P2 and conserved C4) revealed that phi B531 and phi B557 were identical each other, but phi B122 differed from them in 5 gene sequences, the xis gene content and the virion protein profile. Thus, phi B122 represents a new type of still undescribed ETA-converting phage. This study highlights not only the conclusive genomic diversity of eta gene-positive phages, but also their virulence implications in impetigo S. aureus strains.
Keywords: Staphylococcal Infections; Staphylococcus aureus; Staphylococcus Phages; pemfigus; Humans; stafylokokové bakteriofágy; stafylokokové infekce; Molecular Sequence Data; molekulární sekvence - údaje; Disease Outbreaks; lidé; přenos genů horizontální; Gene Transfer, Horizontal; genetická variace; Genetic Variation; Exfoliatins; Czech Republic; Česká republika; exfoliatiny; Pemphigus; epidemický výskyt choroby